Business Center Facility to Foster Entrepreneurial Interest at Vocational High School Students - Suyatmini; Setyaningrum, Dea Yesiana; Prastika, Anis Nurma (Proceedings International Conference on Education Innovation and Social Science, 2022)
This research aims to describe the business center facility at Vocational High School of Surakarta City, Central Java, Indonesia to foster students’ entrepreneurial interest. It was qualitative research with an ethnographic design. The data were collected by means of observation, interviews, and documentation. The data validity was carried out by triangulation of sources and techniques. The data were analyzed by using an interactive model with the steps of data collection, data reduction, data presentation, and conclusion/ verification. The findings showed that the business center facility at Vocational High School of Surakarta in the form of a shop/minimarket located in the front yard of the school used as a place for students’ business learning to provide various kinds of goods and products. The business center was managed by the appointed teachers from the school. Fostering entrepreneurial interest through the business center facility was performed by encouraging entrepreneurial values implemented in practice through Creative Products and Entrepreneurship subject, or display subject. Students’ confidence was shown in how they serve consumers. Students’ creativity was shown in how they determine product ideas and arrange goods. Students oriented to tasks and results by carrying out the practice enthusiastically and obtaining rewards from the teachers. Students’ leadership was formed by applying personal selling in the implementation of practice, time discipline, discipline in displaying goods, and mentoring from entrepreneurship teachers and business center managers directly in the implementation of practice.